Лесные загадки: сказки и рассказы / Ю. Д. Дмитриев ; худож. В. Бастрыкин - Дмитриев Юрий Дмитриевич (Внеклассное чтение, 2007)
Экземпляры: аб. (2008) / Инвентарный номер: 51973 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 53 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4